Application of molecular markers for genetic discrimination of Fusarium wilt pathogen races affecting chickpea and pigeonpea in major regions of India - Datta, J.; Lal, N. (Cellular and Molecular Biology, 2012)
(foc) and Fusarium udum (Fud) collected from major pulse growing regions of India. Out of 247 bands produced by 24 Randomly Amplified Polymorphic DNA (RAPD) primers in Foc isolates, 210 (85%) were polymorphic. A maximum of 14 amplicons were generated by primer OPF 05 whereas minimum 7 amplicons were generated by primer K7. A total of 24 alleles were produced by twelve Simple Sequence Repeats (SSR) primers with an average of two alleles per marker in foc isolates. The maximum number of 4 alleles was obtained with primer SSR 12. SSR amplicon size ranged from 100 to 400 bp. The Unweighted Pair Group Method with Arithmetic average (UPGMA) cluster analysis based on RAPD and SSR profiles grouped the fourteen foc isolates into four major clusters. The universal Inter Transcribed Spacer (ITS) primer pair amplified 630 bp bands in all fourteen foc isolates while significant length polymorphism was obtained only when analysed by restriction digestion with EcoRI and MspI enzymes. The cluster analysis of ITS-RFLP grouped all 14 Foc isolates into three major clusters. Twenty four RAPD primers generated a total of 226 bands (ranging 0.3 to 3.0 kb) in Fusarium udum with an average of 9.4 bands per primer and a total of 27 alleles were produced by twelve SSR primers with an average of 2.25 alleles per marker. All isolates amplified a single band ranging from 100 to 450 bp. The universal ITS primer pair amplified 650 bp bands in all fourteen fud isolates while significant length polymorphism was obtained only when analysed by restriction digestion with EcoRI and Hind III enzymes. The cluster analysis of ITS-RFLP grouped all 14 Fud isolates into three major clusters. The cluster analysis using various markers show the grouping of Fusarium isolates strictly according to their cultural characteristics and degree of pathogenicity and not the geographical origin. This information will be helpful for pathologists and plant breeders to design effective resistance breeding programs in chickpea and pigeonpea taking into account the diversity in wilt pathogen.